The Inheritance of Kompang to The Recent Generation of Malay Society in Riau - Lestari, Yunia Murdi; Florentinus, Totok Sumaryanto; Utomo, Udi (Universitas Negeri Semarang, 2019)
Kompang is a traditional music and the inheritance for Malay people. In the era of globalization, the necessity of artistic entertainment dynamically changes. Hence, the transfer of the arts through generation is an obligation to preserve the tradition. Therefore, this research aims to analyze the process of inheritance of Kompang to the recent generation of Malay society in Riau through formal and informal methods. Formal education is in relevance to schooling and skill training. Informal education has a correlation with enculturation and socialization. The factors of the inheritance of Kompang in the industrial area are the diversity of the demography and the influences of globalization. In regards to the process, the researcher employed interdisciplinary approaches under the fields of sociology to analyze the artistic activities of the society in general. The research works under the a case study design using observation, interview, and document study as the methods of gathering data. In order to analyze the data, the researcher used interactive data analysis through data reduction, presentation, and verification. The implication of this research is the expectation of growing the sensibility of Malay community in Riau to preserve the existence of Kompang as a traditional music.